1990
DOI: 10.1037/h0092462
|View full text |Cite
|
Sign up to set email alerts
|

Associative factors in tolerance to analgesia produced by electrical stimulation in the brainstem.

Abstract: Tolerance to the analgesic effects of electrical stimulation of the periaqueductal gray was confirmed, and it was demonstrated that this effect was mediated by environmental conditional stimuli (CSs). First, tolerance was extinguished after repeated presentation of CSs in the absence of brain stimulation. Second, environment-specific tolerance was demonstrated. Analgesia was reinstated after brain stimulation in a different test environment. Omission of brain stimulation in the stimulation environment failed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…86 -92 However, other studies found no evidence for the development of associative hyperalgesia. [93][94][95][96] Several investigators pointed out that the specific drug administration algorithm and nociceptive assay may be decisive factors determining whether associative hyperalgesia is expressed. 86,97,98 Mechanisms underlying associative hyperalgesia are poorly understood, although one study suggested that NMDA receptors may mediate it.…”
Section: Animal Studiesmentioning
confidence: 99%
“…86 -92 However, other studies found no evidence for the development of associative hyperalgesia. [93][94][95][96] Several investigators pointed out that the specific drug administration algorithm and nociceptive assay may be decisive factors determining whether associative hyperalgesia is expressed. 86,97,98 Mechanisms underlying associative hyperalgesia are poorly understood, although one study suggested that NMDA receptors may mediate it.…”
Section: Animal Studiesmentioning
confidence: 99%